AGRICULTURE AND APPLIED STATISTICS-I - P.K. SHAHU; P.K. SHAHU (New Delhi Kalyani, 2007)
This book is an attempt to explain various theories of statistics which can be used in solving numerous related problems.
Statistics its application Probability Theory its applications Sampling Techniques Statistcal Inference Correlation Analysis
Keywords: Agriculture Statistics